Effect of Phosphate Source on Growth of Chlorella vulgaris Cultured with Indole-3-Acetic Acid-Producing Bacteria - Lintang Guritno Cucu Wijaya; Sitoresmi Prabaningtyas (Jurnal Ilmiah Sains, 2024)
The need for energy sources in Indonesia continues to increase, in 2018 Indonesia is a country with energy consumption of around 114 Million Tons of Oil Equivalent (MTOE). Therefore, alternative energy from biomass such as biodiesel is needed. Chlorella vulgaris is a microbe suitable for alternative energy because it contains up to 80% lipids. Chlorella vulgaris needs phosphorus for cell growth from fertilizer for the production of Adenosine Triphosphate (ATP). In addition to phosphorus, co-cultures with IAA-producing bacteria can promote the growth of C. vulgaris.  This study was conducted to evaluate the influence of phosphate sources on the growth  of C. vulgaris cultured with IAA-producing bacteria. This study was carried out by co-culture C. vulgaris and IAA-producing bacteria with different phosphate sources on Gusrina medium for 27 days. The treatment consisted of treatment A (control), B Triple Super Phosphate (TSP), and C Super Phosphate-36 (SP-36). Cell growth was calculated using  the Petroff-Hausser counting chamber method  followed by the ANOVA test. The highest cell growth was obtained in treatment B (TSP), followed by treatment C (SP-36), and finally treatment A (control). The results showed that the addition of phosphate sources had an effect on the growth  of C. vulgaris with the highest number of cells found in treatment B (TSP) of 2,66 × 106 cells/mL. Keywords: Chlorella vulgaris; co-culture; phosphorus